Comparative analysis of mechanical and water absorption behaviour of jute/glass fibre reinforced epoxy and polyester hybrid composites. (2018) - Karthick, R.; Anbumalar, V.; Sutharson, B.
In this work, various combinations of composite specimens made up of epoxy/polyester matrices reinforced with hybrid jute and glass fibres. Mechanical properties such as tensile, impact, flexural and hardness strength and water absorption properties were evaluated and discussed. Hand layup technique was used to fabricate composite specimen. Totally six composite specimens were prepared by different composition of fibres and resins. Three specimens were prepared by different weight percentage of jute fibre, glass fibre and epoxy and remaining three specimens were prepared by polyester resin for same weight percentage of jute and glass fibre. From the result, it is observed that, the composite specimen which is prepared using epoxy resin obtained the better mechanical properties than polyester resin. In water absorption test, ordinary, sea and distilled water were used to perform the water absorption test. Ordinary water obtained the highest % of water absorption than sea and distilled water.